Kandungan Logam Berat dalam Tanah pada Daerah Sekitar Penambangan Emas di Sungai Kuantan - Rindi Genesa Hatika (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2022)
This study aims to determine the heavy metal content contained in the soil in the area around the gold mining in the Sungai Kuantan, Kabupaten Kuantan Singingi, Riau. There was 4 predetermined sampling points using GPS. Analysis of metal content in the soil was performed using Atomic Absorption Spectrophotometer (AAS). The results of the study found that there are heavy metal content in soil samples of Pb, Hg, Zn, As, Cd and Cu. Based on the threshold value of predetermined sediment / soil, the concentration of heavy metals contained in the soil in the area around the gold mining in the kuantan river far exceeds the predetermined threshold.